Legal Issues in the Supervision and Enforcement of Professional Ethics for Advocates in Indonesia - Raharjo, Budi; Putra, Rengga Kusuma; Kossay, Methodius (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The supervision and enforcement of the advocate code of ethics in Indonesia continue to face various challenges, impacting the effectiveness of the existing regulatory framework. The number of ethical violations committed by advocates has been increasing, from 120 cases in 2018 to 345 cases in 2023, with the most prevalent infractions including conflicts of interest, abuse of authority, and gratification. One of the primary factors contributing to the weak enforcement of the code of ethics is the limited oversight system, which remains confined to advocate organizations without the involvement of independent institutions. This study aims to analyze the effectiveness of the advocate supervision system in Indonesia, compare it with best practices in other countries, and identify measures that can be implemented to enhance accountability and transparency within the profession. The research employs a normative legal method with a comparative law approach and empirical studies. The analysis is conducted on existing regulations, case reports on violations, and interviews with key stakeholders, including advocates, clients, and legal observers. The findings reveal that only 40% of reported violations result in strict sanctions, while merely 10% of advocates found guilty of ethical misconduct face license revocation. Additionally, a survey of 500 respondents indicates that only 35% of the public is aware of the complaint procedures against advocates who breach ethical standards, highlighting the low level of transparency in the supervision system. This study contributes to the discourse by recommending the establishment of an independent institution to oversee advocates' compliance with ethical standards, as well as the increased utilization of digital technology in the supervision system. With more transparent and accountable oversight reforms, it is expected that ethical violations within the legal profession can be minimized, thereby strengthening public trust in Indonesia’s legal system